Biopriming Potential Screening of Endophytic Bacteria to Prevent Amorphophallus muelleri Blume Agaist Soft Rot Disease Through In-vitro and In-Planta Screening - Ely Maghfiroh; Ika Roostika; Deden Sukmadjaja; Abdul Munif; Abdjad Asih Nawangsih; Alina Akhdiya (Bogor Agricultural University, Indonesia, 2026)
Soft rot is the serious problem in cultivation and post harvest of A. muelleri Blume Yam (Elephant foot Yam). This experiment aims is to screen and characterize endophytic bacteria that potentially prevent soft rot on porang (A. muelleri Blume) through in-vitro and in-planta screening. Screening of the bacteria resulted three isolates i.e. EAP10, EAP17, and Bacillus velezensis EG113 could inhibit soft rot caused by P. carotovorum B4. The three isolates demonstrated that EAP10, EAP17, Bv EG113 have anti quorum sensing (AQS) activity against Chromobacter violaceum and have capability to decrease the soft rot incidence of porang plantlets artificially infected with Pectobacterium carotovorum B4. Compared to the other selected endophytes, B. velezensis EG113 showed the best capability to decrease the disease incidence (75%). Physiological characterization of the selected endophytic isolates showed cellulolytic, proteolytic, and IAA production capability. The 16S rRNA sequences homology analysis of endophytic isolates showed similarity to Acinetobacter radioresistance (100%) and Bacillus aryabhattai (99%) or Priestia aryabhattai (revision name) respectively for EAP10 and EAP17 isolates. The results suggested that B. velezensis EG113 is potentially to be develop as biopriming agent for early protection of porang.